Rapid generation of hierarchical nanoarchitectures of CdS via facile microwave assisted hydrothermal/semi-solvothermal route - Shinde, Manish D.; Pawar, Amol U.; Sreeja, V.; Rane, Sunit; Potdar, Hari S.; Amalnerkar, Dinesh P. (International Journal of Nanotechnology, 2010)
1-D nanorod bundles as well as sea urchin and starfish like hierarchical morphological nanoarchitectures of CdS have been synthesised using a facile microwave assisted hydrothermal/semi-solvothermal technique. Observation of interesting regular/irregular pine-tree like secondary growth over these hierarchical nanoarchitectures is an important aspect of this work. Cadmium acetate and thiourea were used as precursor materials and were dissolved in solution containing mixture of diethylene triamine (DETA) and deionised water (DIW) in different volume ratios prior to subjecting the resultant solution to microwave radiation of 300 W at a reaction time of 10 min and temperature of 140 degrees C. XRD revealed formation of hexagonal CdS with strong (002) preferred orientation (c-axis orientation). Morphology dependent optical properties are studied using room temperature photoluminescence spectroscopy. We feel such secondary growth will be highly favourable in determining the non-linear properties of optoelectronic devices fabricated using such novel hierarchical nanoarchitectures.
Keywords: CdS; hierarchical nanoarchitectures; Microwave; Nanorods; secondary growth; solvothermal synthesis

CO2 Laser direct written MOF-based metal-decorated and heteroatom-doped porous graphene for flexible all-solid-state microsupercapacitor with extremely high cycling stability - Basu, Aniruddha; Roy, Kingshuk; Sharma, Neha; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Rane, Sunit; Rode, Chandrashekhar V.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2016)
Over the past decade, flexible and wearable microelectronic devices and systems have gained significant importance. Because portable power source is an essential need of such wearable devices, currently there is considerable research emphasis on the development of planar interdigitated micro energy-torage devices by employing diverse precursor materials to obtain functional materials (functional carbon, oxides, etc.) with the desirable set of properties. Herein we report for the first time the use of metal organic framework (MOF) and zeolitic imidazolate framework (ZIF-67) for high-wavelength photothermal laser direct writing of metal-decorated, heteroatom-doped, porous few-layer graphene electrodes for microsupercapacitor application. We argue that the specific attributes of MOF as a precursor and the high-wavelength laser writing approach (which creates extremely high localized and transient temperature (>2500 degrees C) due to strong absorption by lattice vibrations) are together responsible for the peculiar interesting properties of the carbon material thus synthesized, thereby rendering extremely high cycling stability to the corresponding microsupercapacitor device. Our device exhibits near 100% retention after 200 000 cycles as well as stability under 150 degrees bending.

Concurrent synthesis of SnO/SnO2 nanocomposites and their enhanced photocatalytic activity - Roy, Animesh; Arbuj, Sudhir; Waghadkar, Yogesh; Shinde, Manish; Umarji, Govind; Rane, Sunit; Patil, Kashinath; Gosavi, Suresh; Chauhan, Ratna (Journal of Solid State Electrochemistry, 2017)
The SnO/SnO2 nanocomposites were synthesized using semisolvothermal reaction technique. These nanocomposites were prepared using different combination of solvents viz., ethanol, water, and ethylene glycol at 180 A degrees C for 24 h. The synthesized nanocomposites were analyzed with various characterization techniques. Structural analysis indicates the formation of tetragonal phase of SnO2 for the sample prepared in ethanol, whereas for other solvent combinations, the mixture of SnO and SnO2 having tetragonal crystal structures were observed. The optical study shows enhanced absorbance in the visible region for all the prepared SnO/SnO2 nanocomposites. The observed band gap was found to be in the range of 3.0 to 3.25 eV. Microstructural determinations confirm the formation of nanostructures having spherical as well as rod-like morphology. The size of nanoparticles in ethanol-mediated solvent was found to be in the range of 5 to 7 nm. Thermogravimetric analysis indicate the weight gain around 1.3 wt% confirming the conversion of SnO to SnO2 material. The photocatalytic activity of synthesized nanocomposites was evaluated by following the aqueous methylene blue (MB) degradation. The sample prepared in ethylene glycol-mediated solvent showed highest photoactivity having apparent rate constant (K-app) 0.62 x 10(-2) min(-1).
Keywords: Dye-degradation; Nanocomposite; Photocatalysis; tin oxide